2021
DOI: 10.1590/pboci.2021.008
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Preferred Mode of Getting Information on First Aid Management of Avulsed Permanent Teeth: Survey of Nigerian Mothers

Abstract: Objective: To determine the awareness and sources of information on first aid management of avulsed permanent teeth in a group of South-western Nigerian mothers. Material and Methods: An 18-item interviewer-administered questionnaire was used to survey 385 mothers attending the antenatal and immunization clinics on their perception towards dental avulsion, its management, sources, and preferred mode of receiving information on first aid. The effect of all significant factors was inferred at p<0.05. Results: Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
2
2
0
1
Order By: Relevance
“…Findings of this study unveiled that a significant majority (92%) of the participants lacked any type of pre-hospital education regarding the management of avulsed teeth. This high percentage is consistent with research conducted by Jain et al [12], Shashikiran et al [14], Loo et al [10], Ningthoujam et al [13], Abdellatif and Hegazy [18], Olatosi et al [16]; [19] in Davangere, India, Bhopal, India, and Imphal, India, respectively. Five of the seven participants who possessed prior education on the subject cited a health professional or dentist as their source.…”
Section: Education On Pre-hospital Management Of Avulsed Toothsupporting
confidence: 89%
See 3 more Smart Citations
“…Findings of this study unveiled that a significant majority (92%) of the participants lacked any type of pre-hospital education regarding the management of avulsed teeth. This high percentage is consistent with research conducted by Jain et al [12], Shashikiran et al [14], Loo et al [10], Ningthoujam et al [13], Abdellatif and Hegazy [18], Olatosi et al [16]; [19] in Davangere, India, Bhopal, India, and Imphal, India, respectively. Five of the seven participants who possessed prior education on the subject cited a health professional or dentist as their source.…”
Section: Education On Pre-hospital Management Of Avulsed Toothsupporting
confidence: 89%
“…This current study revealed that about two-thirds of the participants did not know about the possibility of replantation of an avulsed permanent tooth. This is similar to studies done in Chennai, India [14], Saudi Arabi [15], and Nigeria [16] where a greater percentage of the participants were also not aware of the possibility of replantation of an avulsed tooth. However, this finding contrasts with studies done by Jain et al in 2017 [12], Bhopal, and Ningthouiam [13] in India where a greater percentage of the participants were aware that avulsed permanent tooth could be replanted.…”
Section: Awareness About Replantation Of Avulsed Permanent Toothsupporting
confidence: 86%
See 2 more Smart Citations
“…Hussain et al 32 Avulsão dentária -Cuidados com o reimplante, armazenamento, quando levar ao serviço de emergência. Habeeb et al 36 Asfixia, afogamento e queimadura -Cuidados com queimaduras e como retirar roupas aderidas. Como realizar as manobras de desengasgo de criança.…”
Section: Introductionunclassified